MODEL DEFORMASI GETAS DI ZONA SESAR KALIGARANG, SEMARANG - Fahrudin, Fahrudin; Winarno, Tri (Jurnal Geologi dan Sumberdaya Mineral, 2012)
Tectonic activities in Semarang have resulted fault formations. A proper identification on faults and subsidiary structures will provide understanding on the kinematic and dynamic of the Kaligarang Fault. The Kaligarang Fault Zone has been formed since the Tertiary time with stress system orientation of σ1 = 37°, N158°E, σ2 =,45°, N12°E, σ3 = 30°, N244°E indicating left lateral displacement. Afterwards during Plio-Plestocene, the Kaligarang Fault Zone was reactivated with right lateral displacement as indicated by stress system orientation of σ1 = 51°, N185°E, σ2 = 30°, N205°E, σ3 = 8°, N275°E. Beside that, the linements at surroundings of the Kaligarang Fault have NEE-SWW until NWW-SEE directions. This structures were caused by the Unggaran activities.Keywords: Kaligarang Fault, stress system, reactivated, left lateral right lateral